Cyberidentities Canadian and European Presence in Cyberspace - D'Haenens, Leen (International Canadian Studies Series, 1999)
This innovative study explores diverse aspects of Canadian and European identity on the information highway and reaches beyond technical issues to confront and explore communication, culture and the culture of communication.